THE EFFECT OF WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE THROUGH WORK STRESS AND WORKLOAD - Dwitanti, Errica; Murwani, F. Danardana; Siswanto, Ely (International Journal of Business, Law, and Education, 2023)
This study aims to investigate the effect of work-life balance on employee performance through work stress and workload at PT. Bank Negara Indonesia (Persero), Tbk. Brawijaya Branch Office. Work-life balance is a balance between the demands of work and personal life owned by employees. Work stress refers to the level of pressure and stress experienced by employees due to heavy work demands, while the workload is the workload faced by employees in carrying out their work tasks. The research method used is a survey with a questionnaire distributed to employees at the Brawijaya Branch Office. The data collected was then analyzed using statistical techniques to identify the relationship between the variables studied. The results showed that work-life balance has a positive effect on employee performance at PT. Bank Negara Indonesia (Persero), Tbk. Brawijaya Branch Office. In addition, work stress and workload have also proven to have a significant effect on employee performance, where high work stress and workload tend to reduce employee performance. In further analysis, this study also found that work-life balance functions as a mediator between work stress and workload and employee performance. That is, a good work-life balance can help reduce the level of work stress and workload experienced by employees, which in turn increases their performance. This research provides a further understanding of the importance of work-life balance in improving employee performance in the work environment of PT. Bank Negara Indonesia (Persero), Tbk. Brawijaya Branch Office. The implications of this finding can help management to implement policies and programs that support a balanced work-life balance to improve employee welfare and productivity. However, keep in mind that other factors can also affect employee performance and could be an area of further research